2017
DOI: 10.1039/c6ra25447k
|View full text |Cite
|
Sign up to set email alerts
|

Donor–acceptor single cocrystal of coronene and perylene diimide: molecular self-assembly and charge-transfer photoluminescence

Abstract: The research on donor-acceptor (D-A) cocrystalline structures based on organic semiconductive molecules has drawn great attention due to their unique optical and electronic properties. Among the building block molecules, derivatives of perylene-3,4,9,10-tetracarboxylic-3,4,9,10-diimides (PTCDI) are of particular interest as these molecules form high performance n-type semiconductors with strong air stability. However, the cocrystal of PTCDIs remains challenging to fabricate, and only few D-A cocrystals of PTCD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 38 publications
2
39
0
Order By: Relevance
“…species (Δ ν ≈2 cm −1 ), indicating the existence of charge transfer between Cor and NDI after co‐assembly . However, the C=O stretching vibrations of NDI exhibit a blue‐shift (IR: Δ ν ≈5 cm −1 ; Raman: Δ ν ≈2–6 cm −1 ), which can be attributed to the weakened hydrogen bonding (−C=O⋅⋅⋅H) in the co‐crystal with an elongating distance (2.623 Å between adjacent NDI and Cor., Figure d) compared with that in pure NDI (2.386 Å for NDI‐NDI; Supporting Information, Figure S8) . Notably, this CT transition has induced a significant photophysical property.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…species (Δ ν ≈2 cm −1 ), indicating the existence of charge transfer between Cor and NDI after co‐assembly . However, the C=O stretching vibrations of NDI exhibit a blue‐shift (IR: Δ ν ≈5 cm −1 ; Raman: Δ ν ≈2–6 cm −1 ), which can be attributed to the weakened hydrogen bonding (−C=O⋅⋅⋅H) in the co‐crystal with an elongating distance (2.623 Å between adjacent NDI and Cor., Figure d) compared with that in pure NDI (2.386 Å for NDI‐NDI; Supporting Information, Figure S8) . Notably, this CT transition has induced a significant photophysical property.…”
Section: Resultsmentioning
confidence: 90%
“…[45,46] However,t he C=Os tretching vibrations of NDI exhibit ab lueshift (IR: Dn % 5cm À1 ;Raman: Dn % 2-6 cm À1 ), which can be attributed to the weakened hydrogen bonding (ÀC=O•••H) in the co-crystal with an elongating distance (2.623 between adjacent NDI and Cor.,F igure 2d)c ompared with that in pure NDI (2.386 for NDI-NDI;S upporting Information, Figure S8). [47] Notably,t his CT transition has induced as ignificant photophysical property.A sp resented in Figure 3b and g, the ternary cocrystal NCT displays an excited red luminescence (a broad peak appeared at ca. 640 nm), which is significantly bathochromically shifted compared to those of individual components (Supporting Information, Figure S9).…”
Section: Resultsmentioning
confidence: 99%
“…The sensor performance against environmental factors such as temperature, humidity and concentration, and in correlation with the thermodynamic parameters of analytes like boiling point, has also been studied in detail, aiming to further improve the robustness and sustainability of sensor system as desired in practical use [23]. The environmental factors may also affect the intermolecular association of PIs aggregates, thus causing change in sensing performance [48,49].…”
Section: Physicochemical and Optical Properties Of Pismentioning
confidence: 99%
“…Organic donor-acceptor (D-A) co-crystals have been shown to possess many interesting properties, among them: semiconducting behavior with appreciable ambipolar charge transport capabilities, [1][2][3][4][5][6][7][8] tunable emission spectra, 5,[9][10][11][12][13] and ferroelectricity. 5,9,14 These structures are also believed to be good candidates for organic eldeffect transistors, 15,16 organic photovoltaics, [17][18][19] photonic logic, 20,21 and near-IR photothermal imaging.…”
Section: Introductionmentioning
confidence: 99%
“…[26][27][28][29] Several studies characterizing the CT ground state optical absorption as well as the steady-state and time-resolved photoluminescence of D-A co-crystals have been reported. 2,11,12,20,21,30,31 Also, studies using ultrafast transient diffuse reectance spectroscopy have been reported on a variety of co-crystal powders, including phenathrene 32 and methylated benzenes 33,34 co-crystallized with PMDA, and aromatic donors co-crystallized with tetracyanobenzene 35,36 and tetracyanoquinodimethane 37 acceptors. In addition, there have been several studies of exciton transport in polyacene single crystals of interest to singlet ssion.…”
Section: Introductionmentioning
confidence: 99%